The Influence of Age on Emotional Intelligence Among NGO Leaders in Addis Ababa, Ethiopia - Kere, Zerihun Awano (Universitas Syiah Kuala, 2024)
This study investigates how age influences emotional intelligence (EI) among 144 leaders working in non-governmental organizations (NGOs) based in Addis Ababa, Ethiopia. Emotional intelligence is crucial for effective leadership, as it helps leaders understand and manage their own emotions and those of others. Building on recent research emphasizing the importance of EI in leadership, an attempt was made to explore whether age plays a role in shaping EI levels among NGO leaders. To answer this question, the ANOVA (Analysis of Variance) test was employed to analyze the data in comparing the EI scores of leaders across different age groups based on their age. The results of the analysis revealed significant differences in EI scores among NGO leaders of different ages indicating that older leaders tend to exhibit higher levels of emotional intelligence. This suggests that older leaders may have different emotional skills compared to younger leaders. These findings highlight the importance of considering age-related differences in EI when assessing leadership effectiveness within NGOs. By understanding how age influences EI, organizations can better tailor their leadership development programs to meet the diverse needs of leaders across different age groups. Ultimately, this research contributes to our understanding of the complex interplay between age and emotional intelligence in the context of NGO leadership